2018
DOI: 10.1177/1362168818813668
|View full text |Cite
|
Sign up to set email alerts
|

The role of task sequencing in fluency, accuracy, and complexity: Investigating the SSARC model of pedagogic task sequencing

Abstract: This study set out to test the theoretical premise of the SSARC model of pedagogic task sequencing, which postulates that tasks should be sequenced for learners from cognitively simple to complex. This experiment compared the performance of three tasks differing in cognitive complexity in a simple–complex sequence versus in the absence of any other tasks. There were two groups in the study: (1) participants who performed the three tasks in the simple–complex sequence, and (2) participants who performed either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 51 publications
2
25
0
7
Order By: Relevance
“…The major thrust of this study was to explore the effects of task sequencing on multilingual learners' written production in accordance with the SSARC model. Given that past studies tested the role of the SSARC model in L2 oral production (Baralt, 2014;Malicka, 2014Malicka, , 2018, finding that the simple-to-complex order led to significant gains in L2 production over the short or long term, the current study examined the effectiveness of the SSARC model in L2 written production using a simple-complex task design. The results demonstrated that simple-complex task sequencing favoured syntactic and lexical complexity, promoted accuracy, and assisted fluency, providing empirical evidence supporting the theoretical claim of the SSARC model regarding the beneficial role of simple-complex task sequencing for L2 written production.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The major thrust of this study was to explore the effects of task sequencing on multilingual learners' written production in accordance with the SSARC model. Given that past studies tested the role of the SSARC model in L2 oral production (Baralt, 2014;Malicka, 2014Malicka, , 2018, finding that the simple-to-complex order led to significant gains in L2 production over the short or long term, the current study examined the effectiveness of the SSARC model in L2 written production using a simple-complex task design. The results demonstrated that simple-complex task sequencing favoured syntactic and lexical complexity, promoted accuracy, and assisted fluency, providing empirical evidence supporting the theoretical claim of the SSARC model regarding the beneficial role of simple-complex task sequencing for L2 written production.…”
Section: Discussionmentioning
confidence: 99%
“…Following the SSARC model of task sequencing and the times set in the pilot study, the first group performed the written tasks in the simple-to-complex order with 5-minute intervals; participants performed the simple task in 17.2 minutes with 10 minutes of planning time, then the same task in 23.8 minutes without planning time, and finally the complex one in 30.2 minutes without planning time. Similar to Malicka's (2018) study, 60 participants in the individual task group were subdivided into three groups of equal size (n = 20); each subgroup completed only one task under the same task conditions as in the sequencing group. Thus, the difference between the two groups is that in the simple ̶ complex group, all participants performed the tasks successively, while in the individual task group, participants in each subgroup completed only one task at a pre-determined cognitive complexity level.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations